PENGENALAN AKUNTANSI DAN PERPAJAKAN BAGI GENERASI MUDA EDUKASI DAN SOSIALISASI DALAM MENINGKATKAN KEPATUHAN PAJAK - SMK IPTEK - Baharuddin Saga; Intan Rahma Sari; Alya Budiantini (Publika Citra Media, 2026)
Awareness of the importance of taxation needs to be instilled from an early age, especially among the younger generation who are future taxpayers. This community service activity aims to provide a comprehensive understanding of accounting fundamentals and tax regulations to the students of SMK IPTEK. The primary focus of this program is to bridge the gap between theories learned in school and real-world industrial practices, as well as to foster moral awareness regarding the contribution of taxes to national development. The method used in this activity is interactive socialization through material presentations, group discussions, and simple tax calculation simulations. The topics cover the basic accounting cycle, an introduction to various types of taxes (such as Income Tax Article 21 and VAT), and digital tax reporting procedures via e-filing. An evaluation was conducted by comparing pre-test and post-test results to measure the improvement in participants' understanding of the presented material. The results of the activity indicate a significant increase in students' understanding of the relevance of accounting in accurate tax reporting. Most participants began to realize that tax compliance is not merely a legal obligation, but a civic responsibility. Through this education, it is expected that SMK IPTEK students will not only possess technical competence in accounting but also maintain high integrity in fulfilling future tax obligations. This socialization serves as a strategic initial step in forming a